Efektivitas Limbah Debu Tembakau sebagai Insektisida Nabati terhadap Ulat Grayak - Yumna Aqilah Khairunnisa; Sholahuddin Sholahuddin; Ato Sulistyo (Universitas Sebelas Maret, 2019)
Botanical pesticides produced from tobacco plants are reported to be the most toxic compared to other types of plants because it contain 2-8% nicotine substances. The objective of this research was to examine the effect of tobacco dust waste extracts and determine the concentration of the most effective tobacco dust waste extract against armyworms. This research was conducted in Laboratory of Pest and Plant Disease and C Green House Faculty of Agriculture Universitas Sebelas Maret Surakarta from April-July 2018. The stages of this study include the multiplication of S. litura test larvae, preparation of botanical insecticides from tobacco dust waste, mortality test, antifeedant test and phytotoxicity test. This study used a completely randomized design with 6 treatments and 4 replications. The results showed that tobacco dust waste was able to increase the mortality of S. litura larvae, but with a slower effect compared to the treatment of profenofos. Feeding barriers are not seen in the test larvae. The phytotoxicity test shows that tobacco dust waste was not toxic to plants. Based on probit analysis, the concentration of tobacco dust waste which was capable of killing 50% of the population of S. litura was equal to 53.10 gL-1.